Exploring Duolingo Application By Efl Learners To Improve Vocabulary Mastery At SMP Negeri 1 Pangalengan - Kurniawan, Bayu (NextGen Education Review Journal, 2024)
In the era of technology where almost every activity we do is not far from the use of existing technology as a means of support in facilitating the activities being carried out, it is important for every individual human being to be able to adapt to technological developments that currently continue to occur endlessly. This technological development penetrates into everything we do, one of which is in the world of education. This research aims to explore the use of the Duolingo application for young learners in order to improve students’ English vocabulary, to make learning more diverse and efficient. The method used in the research process this time is to use qualitative methods, where this method is used to obtain the desired research results by seeking information obtained from teachers and students regarding the use of the Duolingo application by conducting observations to students and teachers. The results obtained were that student activeness increased and students’ ability to communicate also increased after learning to use the Duolingo application. Based on this, the use of the Duolingo application in the classroom has a positive impact on students’ abilities, and has good potential in improving students’ foreign language skills themselves